IMPLEMENTATION OF MEDICAL ACTION APPROVAL (INFORMED CONSENT) BETWEEN THE HOSPITAL WITH CAESAR OPERATION PATIENTS - Meliani, Made; Wise, Thomas N. (EQUALEGUM International Law Journal, 2023)
Background. Health is one factor most important in implementing development nationally because health is a necessity that is very basic and needed by every human. This research aimed to answer problems regarding implementation procedures approval for medical action (informed consent) between the hospital and the patient giving birth in hospitals, the hospital is responsible for defaults committed by internal doctor implementation of approval for medical procedures. Research Method. This research includes empirical legal research descriptive in nature using primary and secondary data types. Findings. The results of this research contain procedures for implementing medical action agreements between the hospital and the patient who gave birth in the maternity ward of the X Hospital and who had fulfilled the requirements for valid approval of Article 45 of Law No. 29 of 2004 concerning medical practice. However, there are still several obstacles to implementing consent for medical procedures on patients who gave birth at the X Hospital, especially regarding the explanation of the information, form, and content of the informed consent Conclusion. The hospital can provide policies regarding the form and content of informed consent used so that it does not hinder the implementation of the agreement.